Burrowing nematode (Radopholus similis) abundance, distribution and agronomic impact on bananas in Kirinyaga County, Kenya - Gatheru, P.; Thagana, W. M.; S. B., Nchore (International Journal of Horticultural Science, 2026)
Burrowing nematodes (Radopholus spp.) are the most significant parasites of bananas (Musa spp.) world over. They feed on the root tissue of bananas resulting to toppling disease at the fruit bearing stage. This study assessed the impact of farmers selected agronomic practices that influenced distribution of burrowing nematodes. We also assessed the abundance of Radopholus spp. across four AEZs namely; UM 2, UM 3, LM 3 and LM 4 of Kirinyaga County, Kenya. Purposive sampling was done on April, 2024 targeting farmers that grew ‘dwarf Cavendish’ variety of bananas, those that grew an average of 25 banana stems and those whose farms that were 1km apart. A structured questionnaire was issued to ninety farmers to collect demographic information and to determine their awareness of burrowing nematodes and toppling disease. Soil and banana root samples were also collected to determine abundance and distribution of burrowing nematodes. Data from the questionnaire and samples was subjected to R -statistical software and analysed at p≤ 0.02. The study revealed that majority of banana farmers practised mixed cropping and were not aware of toppling disease associated with Radopholus spp. It also revealed that majority of banana farmers were male and of ˃ 50 years of age. The findings also showed Radopholus spp was rarely distributed in lower AEZs of LM 3 and LM 4 compared to Pratylenchus spp. which was pre- dominantly distributed in upper AEZs of UM 2 and UM 3 in both soil and root samples.